Knowledge, attitude and practice of antenatal exercise among pregnant women in Kuala Selangor - Nur Farhana, Md Yunus; Rosliza, Abdul Manaf; Suriani, Ismail; Parwathi, Alagirisamy; Romizan, Jathin (Penerbit Universiti Sains Malaysia, 2025)
Background: Pregnancy is associated with significant physical, emotional, and psychological changes. To adapt to these changes and ensure a healthy pregnancy, lifestyle interventions such as regular antenatal exercise (ANE) are vital. Hence, adequate knowledge of ANE among pregnant women is essential to promote the uptake of ANE. This study aimed to assess the knowledge, attitude, and practice (KAP) of ANE, and its associated factors among pregnant women in a suburban district. Methods: A cross-sectional study was conducted among 571 pregnant women receiving antenatal care at primary health clinics in Kuala Selangor. Demographic data and maternal characteristics, as well as the KAP and associated factors of ANE, were obtained using a self-administered questionnaire. Descriptive statistics of the KAP of ANE were generated. Binary and multivariate logistic regressions were used to determine the predictors of ANE among pregnant women. Results: About half (53.7%) of the study participants reported adequate knowledge while two-thirds (65.5%) had a positive attitude toward exercise. However, only 38.9% displayed a good practice of ANE. KAP of ANE was significantly associated with higher education, pre-pregnancy physical activity, and having received advice on physical activity. Women with positive attitudes were more likely to have good practice of ANE (AOR = 2.2; 95% CI: 1.5–3.2). Conclusion: In short, this study indicated a moderate level of knowledge but a positive attitude towards ANE among pregnant women. Nevertheless, their actual practice of ANE needs to be improved. Future health education campaigns should focus on empowering women about the uptake and conduct of physical activity during pregnancy.